Adolescents' exposure to tobacco and alcohol content in YouTube music videos - Cranwell, Jo; Murray, Rachael; Lewis, Sarah; Leonardi-Bee, Jo; Dockrell, Martin; Britton, John (Wiley, 2015)
AIMS: To quantify tobacco and alcohol content, including branding, in popular contemporary YouTube music videos; and measure adolescent exposure to such content. DESIGN: Ten-second interval content analysis of alcohol, tobacco or electronic cigarette imagery in all UK Top 40 YouTube music videos during a 12-week period in 2013/14; on-line national survey of adolescent viewing of the 32 most popular high-content videos.